Modelo matemático para planejamento da circulação de trens em uma ferrovia de linha singela - Pereira, Edson Pimentel (2015)
Several factors have contributed to the increasing demand for rail transportation in Brazil. Among them we can mention the increase of Brazilian exports in recent years and the approval of the new regulatory framework for the Brazilian railway sector that allowed the use of the railways idle capacity and the sharing of the rail tracks by several operators. Investments for construction of new railways and improvements on existing ones are very high, making it difficult to implement new projects. Therefore, it is necessary to improve train circulation planning in order to increase capacity without the need for new investments, thus optimizing the existing structure. This paper proposes a mathematical model to carry out the planning of train circulation on a single line railroad that minimizes the transit time, e.g., the total travel of all trains, and consequently reduces the time stopped at the crossing yards. The proposed model allows the trains to be delayed or advanced at departure time to reduce time stopped in crossing yards. The model was solved optimally using the solver CPLEX 12.6. Tests were performed with real data from Ferrovia Centro Atlantica (FCA) and the results achieved by CPLEX were compared with the real life planning results of FCA. The model achieved a reduction of the trains travel time in all scenarios tested.